A new genus of Braconinae (Hymenoptera: Braconidae) from India with remarkable head ornamentation - Ranjith, A.p.; Nasser, M.; Rajmohana, K.; Quicke, D. L. J. (Zootaxa, 2016)
A new braconine genus, Stephanobracon Ranjith & Quicke (type-species: Stephanobracon narendrani Ranjith & Quicke sp. nov.) from south India is described and illustrated. It belongs to the tribe Braconini and it displays autapomorphic characters of having two pairs of sharp protuberances near to the antennal sockets and corrugated protuberances on the lateral part of the frons. Its possible relationship to other braconine genera, notably Dolabraulax Quicke, Simra Quicke and Syntomernus Enderlein, is discussed.